Necessity of the Social Worker in the Educational System - Chica, Tatiana Moreira; Meza, Anicia Katherine Tarazona; ChÃƒÂ¡vez, Sandra Auxiliadora Romero; Quiroz, Mariela Alexandra Moreira (International Research Journal of Management, IT & Social Sciences, 2017)
Portoviejo is named the city of the Valley because it is irrigated by the river of the same name and surrounded by hills, where many people with low economic income and dysfunctional families live, many young people from these areas who are currently studying in the educational units of the city. The research made it possible to survey different teachers of the educational units of the municipality, resulting in the need to incorporate the social worker into the training environment, which allows a work climate to be consolidated and has a positive influence not only over time but in the depth of the intervention and its effectiveness, since the social worker is a fundamental pillar within the educational task and within the teaching-learning process.